AUDIT FEE, TENURE, REPUTATION, AND AUDIT QUALITY: THE ROLE OF AUDIT COMMITTEE - Aa'zza, Azka Al; Rochayatun, Sulis (Jurnal Akuntansi Bisnis, 2026)
Background: To preserve stakeholder trust in corporate financial information, study into audit quality variables is needed due to the frequency of poor audit quality instances in the financial industry. Objective: This study aims to examine the effect of external factors, including audit fees, audit tenure, and auditor reputation, on quality and audit committees as moderators in BEI-indexed financial sector companies. Research Methods: Quantitative and statistical data analysis. The secondary data are from IDX-indexed financial and annual reports for 2022–2024. Research Results: Audit fees improve audit quality, while tenure and reputation do not. Audit committees may reduce the influence of audit fees on audit quality, but not tenure. Audit committees may boost auditor credibility and audit quality. Originality/Novelty of Research: This study adds new features such assessing audit fees using pure audit costs, audit quality using the earnings surprise benchmark, which focuses on profit quality, and studying the financial industry.